Portrait of the journal as a young adult - Grandjean Philippe; Ozonoff David (BMC, 2012)
Abstract Since its founding a decade ago, Environmental Health has received more than one thousand manuscripts. Last year marked the first time we published over 100 articles. The journal web site currently receives over 60,000 unique visitors every month, and the steady increase suggests that the number will soon exceed 100,000 monthly. Individual articles are usually accessed several thousand times within a few years of publication, the highest number for a single paper being close to 100,000. The access numbers suggest that the journal has a reach that goes much beyond narrow academic circles as represented by numbers of citations in scholarly journals. To further the goal of reaching the wider public health community and linking to environmental health promotion, we ask prospective Environmental Health authors to highlight the findings that are new or different along with the implications for future research and in terms of prevention of environmental hazards.